Numerical Simulation of Shock Response and Dynamic Fracture of a Concrete Dam Subjected to Impact Load (2016)
The shock response and dynamic fracture of concrete gravity dams under impact load are the key problems to evaluate the antiknock safety of the dam. This study aims at understanding the effects of impact shock on the elastic response and dynamic fracture of concrete gravity dams. Firstly, this paper uses acceleration records of a concrete gravity dam under impact to establish the correct way to determine the concrete gravity dam of the fundamental frequency and present cut sheets multi-degree-of-freedom dynamic modeling. Under strong impact loading, the constitutive relation of concrete gravity dam and the highest frequency of the impact are uncertain. So, the main advantage of this method is avoiding the use of elastic modulus in the calculation. The result indicates that the calculation method is a reliable computational method for concrete gravity dams subjected to impact. Subsequently, the failure process of dam models was numerically simulated based on ABAQUS commercial codes. Finally, this paper puts forward suggestions for future research based on the results of the analysis.